Carbide transformation in carburised zone of 25Cr35NiNb+MA alloy after high-temperature service. (2nd January 2016) - Liu, Chunjiao; Chen, Xuedong; Chen, Tao; Nie, Defu; Wang, Lu
Abstract : Microstructure evolution due to carburising of a 25Cr35NiNb+MA ethylene pyrolysis furnace tube was investigated after service for approximately 4 years. The microstructure of 25Cr35NiNb+MA alloy was examined by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) equipped with energy-dispersive X-ray spectroscopy and high-resolution transmission electron microscopy (TEM). The results revealed that M23 C6 carbides of the 25Cr35NiNb+MA alloy had coarsened and transformed to M7 C3 carbides with a heavily faulted structure during carburising. The content of M7 C3 carbide increased closer to the inner wall. A large number of dislocations had been observed surrounding the carbides and some formed dislocation walls. The carbide transformation mechanism and the effect of the dislocation walls are discussed.